STRATEGI MANAJEMEN KEUANGAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR ISLAM TERPADU NURUL IMAN PONDOK BAMBU - Khofifah Salma; Husnul Khatimah; Hardiansyah, Hardiansyah (Bajang Institute, 2025)
The aim of this research is to find out Financial Management Strategies in Improving the Quality of Education at the Nurul Iman Pondok Bambu Integrated Islamic Elementary School. In research that uses a qualitative approach. The samples taken by researchers were several teaching staff (school management) and also financial staff. Strategy in general has the meaning of an outline of reference for carrying out actions to achieve the desired targets. Management is a process of planning, organizing, directing and supervising resources to achieve the goals set by an institution. Finance is an activity related to the acquisition and management of funds effectively and efficiently in accordance with the overall objectives of the institution. Financial management is an activity carried out with efforts to obtain funds at minimally regulated costs and manage these funds effectively to achieve the goals of an institution. Quality of education can be interpreted as the school's ability to manage all interrelated components efficiently so as to produce added value and applicable standards. The first result of this research is that financial planning to improve the quality of education is outlined in the form of RAPBS which is held before each new school year begins. The implementation of financial management in improving the quality of education can be seen in the allocation of funds in the RAPBS, namely by allocating funds for extracurricular activities, allocating funds for facilities and infrastructure in madrasahs by adding facilities, repairing and maintaining them